Optimization of extraction method and improvement of growth, physiology, yield and antioxidants properties as affected by chitosan in Ocimum basilicum L. - Zubair, Qazizadah Ahmad (2022)
Sweet basil (Ocimum basilicum L.) is one of aromatic herbs belonging to Lamiaceae family and is widely used in pharmaceutical, culinary and traditional medicine industries. Sweet basil holds high potential and demand in mentioned industries, but biomass production and phytochemical content are still not sufficient to cater the demand. The quantity of the extraction of phytochemical content is depends on the extraction technique. It is therefore, important to increase biomass production and the content of phytochemicals at field level and establish suitable extraction technique, in order to achieve high amount of extraction. Two experiments were carried out with the objectives of (i) to establish a suitable combination of ethanol concentration and temperature in order to obtain high amount of selected antioxidant constituents from sweet basil leaves, (ii) to identify the suitable concentration of chitosan and time of application for improvement of the growth, herbal yield and antioxidant contents in sweet basil at field. In the first experiment, three different concentrations of ethanol (60, 75 and 90% v/v) were combined with three different temperatures (40, 60 and 80˚C) for the extraction of sweet basil leaves. The experiment was arranged in 3 X 3 factorial Complete Randomized Design (CRD) with four replications and three samples per replicate. The result showed that 90%ethanol at 80 ̊C had the highest percentage of extraction yield (11.56%) compared to other treatments. However, extracting dried sweet basil leaves with 60% ethanol at 80 ̊C temperature recorded the highest extraction of total phenolic content (67.02 mg of GAE/g of DE), total phenolic yield (693.5 mg of GAE/100 g of DW), total flavonoid content (44.7 mg of QUE/g of DE), total flavonoid yield (462.52 mg of QUE/100 g of DW) and antioxidant activity (66.8%). Results from the correlation analysis showed a positive relationship between phenolic, flavonoid and antioxidant activity of the extract. Therefore, it is recommended to extract sweet basil leaves using 60% ethanol under 80°C. This combination was applied in the second experiment. In the second experiment, chitosan at four different concentrations (0, 2, 4 and 6 ml/L) were applied at three different application times of (20, 40 and 20 + 40 days after transplanting, DAT) at the field. The experiment was organized in 4 X 3 factorial Randomized Complete Block Design (RCBD) with four replications and five plants per replicate. The results showed an interaction between chitosan concentrations and times of applying on growth, herbal yield and secondary metabolites performance of sweet basil plants. From the results, application of chitosan at concentration of 4 ml/L on 20 DAT gave the highest biomass yield components such as leaf fresh weight and leaf dry weight by 43.45 and 59.71% as well as total content of flavonoid and antioxidant activity by 40.21 and 22.81%, respectively, when compared with the control group. In addition, the same treatment resulted in the highest value of plant height, stem diameter, dry weight of stem per plant, number of leaves per plant, total leaf area per plant, average chlorophyll-a, chlorophyll-b, total chlorophyll, actual chlorophyll and dry weight of root per plant by 40.73, 37.47, 40.38, 25.71, 37.19, 9.90, 37.36, 18.75, 18.86 and 143.97%, respectively compare to the control groups. Besides, correlation analysis showed positive relationship among variables as well as dry weight of leaves with total leaf area (r = 0.96) and total chlorophyll (r = 0.76), the AA with TPC (r = 0.80) and TFC (r = 0.57). Most of the growth and physiology variables positively correlated with biomass yield components. In conclusion, it is recommended that the application of 60% ethanol at 80 ̊C extraction temperature showed greater strength in extracting phenolic, flavonoid and antioxidant activity from sweet basil's leaf. Meanwhile, application of 90% ethanol at 80 ̊C temperature showed greater percentage of extraction yield in comparison to other treatments. Besides, the performance of sweet basil plants at field level could be improved by the application of 4 ml/L chitosan at 20 DAT.